2021
DOI: 10.3390/ijms222111480
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of OXA-48: Insight into Mechanism and Structural Basis of Substrate Recognition and Specificity

Abstract: Class D β-lactamase OXA-48 is widely distributed among Gram-negative bacteria and is an important determinant of resistance to the last-resort carbapenems. Nevertheless, the detailed mechanism by which this β-lactamase hydrolyzes its substrates remains poorly understood. In this study, the complex structures of OXA-48 and various β-lactams were modeled and the potential active site residues that may interact with various β-lactams were identified and characterized to elucidate their roles in OXA-48 substrate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In all cases, we also observed a small amount of a species that was 44 Da smaller than the acyl-enzyme complex. This could result from loss of either carbon dioxide at the C3 position or the hydroxyethyl group at the C6 position of the carbapenem, as was previously reported for their interaction with LDTs from other bacteria and class A, C, and D β-lactamases. , Since acylation was the most efficient with ertapenem, we used this antibiotic to measure the apparent acylation rate constant k 2 , which was found to be 0.22 ± 0.01 h –1 (Figure ); this would result in one acylation event every four and a half hours. These results demonstrated that Ldt Ab is acylated in vitro only by carbapenems, albeit at a very slow rate.…”
Section: Resultsmentioning
confidence: 85%
“…In all cases, we also observed a small amount of a species that was 44 Da smaller than the acyl-enzyme complex. This could result from loss of either carbon dioxide at the C3 position or the hydroxyethyl group at the C6 position of the carbapenem, as was previously reported for their interaction with LDTs from other bacteria and class A, C, and D β-lactamases. , Since acylation was the most efficient with ertapenem, we used this antibiotic to measure the apparent acylation rate constant k 2 , which was found to be 0.22 ± 0.01 h –1 (Figure ); this would result in one acylation event every four and a half hours. These results demonstrated that Ldt Ab is acylated in vitro only by carbapenems, albeit at a very slow rate.…”
Section: Resultsmentioning
confidence: 85%
“…Active site residue R250 has been proposed to play an important role in catalysis by binding to the carboxylate of the substrates 47 . We have observed clear binding of Br − or I − ion interacting with R250 in our halide-soaked OXA-48 WT and OXA-48 AcK73 -imipenem-Br − structures ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…R250 has been proposed to play an important role in catalysis by binding to the carboxylate of the substrates. 34 To further explore whether the binding of halides at R250 is a key driving force for the formation of the inactive acyl intermediate, we performed ITC analysis and showed that the OXA-48 R250A variant no longer responds to the presence of chloride with biphasic features but the nonconserved OXA-48 R214A variant still does (Figure 1h, Figure S8). These data indicate that the binding of chloride to R250 is essential for chloride-induced biphasic kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%